Marcas da identidade docente: vivência, formação e profissão - Sampaio, Fabrício de Sousa (2010)
The research aims to analyze the marks that determine the formation and development of teacher identity. These marks constitute the elements of the crossfire which blocks an emancipatory teaching action. The metaphors used - crossfire and marks - refer to effects, learning, signs and impressions experienced by teachers in the course of their personal and professional life that eventually prevent the formation of an emancipatory identity. We used the methodology of ethnographic case study and the Cultural Studies were taken as a lens to see the identity-in-culture. Besides the open and semi-structured interviews, fragments of life stories and informal conversations, a participant observation was conducted to understand the motivations, conflicts, perspectives, acceptances and directions of teachers about their identity construction processes. The look on human identity theory was based primarily on the works of Bauman (1998, 2005, 2007), Woodward (2008), Hall (2006) and Ciampa (2008). To explain the cultural context of human identification, we used Gentili (2008), Torres (2008), Suarez (2008) and Bauman. The State School of Vocational Education Dom Walfrido Teixeira Vieira was chosen as the research field because it is the first professional school in the city of Sobral and because it has an excellent image in the eyes of the sobralense for its teaching-learning effectiveness. The research subjects were sixteen teachers of whom six participated in the interviews. The loci of observation were the monthly planning sessions, lunch intervals, area and continuing education meetings in the 6th CREDE (Regional Centre for Educational Development). It was concluded that the identity of the teachers who participated in the study remains in crisis and the way out or attitude that is left for teachers is the myth-identity or the identity of palimpsest, a reaction to the impossibility of achieving the identities of their preference.